Get comprehensive solutions to your questions with the help of IDNLearn.com's experts. Discover prompt and accurate answers from our experts, ensuring you get the information you need quickly.

(Quadratic Equation and Algebraic Manipulation)

Question 01: Given the equation [tex]$y^2 - ay - 6 = 0$[/tex] where [tex]$a$[/tex] is a constant, find the expression for [tex][tex]$y$[/tex][/tex] in terms of [tex]$a$[/tex].


Sagot :

To solve the quadratic equation [tex]\( y^2 - a y - 6 = 0 \)[/tex] for [tex]\( y \)[/tex] in terms of the constant [tex]\( a \)[/tex], follow these steps:

1. Identify the coefficients: Compare the given equation to the standard form of a quadratic equation [tex]\( ay^2 + by + c = 0 \)[/tex]. Here, [tex]\( a = 1 \)[/tex], [tex]\( b = -a \)[/tex], and [tex]\( c = -6 \)[/tex].

2. Write down the quadratic formula: The solutions to the quadratic equation [tex]\( ay^2 + by + c = 0 \)[/tex] are given by:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]

3. Substitute the coefficients into the quadratic formula: For our equation [tex]\( y^2 - a y - 6 = 0 \)[/tex], we have:
[tex]\[ y = \frac{-(-a) \pm \sqrt{(-a)^2 - 4(1)(-6)}}{2(1)} \][/tex]

4. Simplify inside the square root:
[tex]\[ y = \frac{a \pm \sqrt{a^2 - 4(1)(-6)}}{2} \][/tex]
[tex]\[ y = \frac{a \pm \sqrt{a^2 + 24}}{2} \][/tex]

5. Write the final solutions: Therefore, the solutions for [tex]\( y \)[/tex] in terms of [tex]\( a \)[/tex] are:
[tex]\[ y = \frac{a - \sqrt{a^2 + 24}}{2} \quad \text{and} \quad y = \frac{a + \sqrt{a^2 + 24}}{2} \][/tex]

So, the expression for [tex]\( y \)[/tex] in terms of [tex]\( a \)[/tex] are:
[tex]\[ y = \frac{a - \sqrt{a^2 + 24}}{2} \quad \text{and} \quad y = \frac{a + \sqrt{a^2 + 24}}{2} \][/tex]